Signal processing for slug flow analysis via a voltage or instantaneous liquid holdup time-series. (June 2021) - Soto-Cortes, Gabriel; Pereyra, Eduardo; Sarica, Cem; Torres, Carlos; Soedarmo, Auzan
Abstract: Slug flow is one of the most observed gas-liquid flow patterns in pipes. Owing to its high occurrence, the estimation of slug characteristics is essential for many engineering processes. The slug flow characterization is usually carried out by models and correlations previously calibrated with experimental data generated by the interpretation of voltage or instantaneous liquid holdup time-series. Historically, this interpretation required algorithms that depended on subjective parameters, which created high dispersion on the data. This paper proposes a new signal processing analysis, which does not require any subjective parameter. A statistical algorithm is used to calculate the film and slug cut threshold values, the disregard cut value to group slug pulses, and the disregard cut value to remove slug pulses, which are required to determine the slug characteristics. An experimental data set was used to validate the proposed methodology. The consistency check process followed two independent ways, both with good results. Based on the performance against the experimental data, the proposed algorithm is recommended for slug flow characterization. Highlights: A novel signal processing methodology for slug flow analysis is developed and validated. The statistical algorithm does not depend on any subjective criteria. The methodology is illustrated using voltage time-series, but it is applicable to instantaneous liquid holdup time-series.